INTEGRITY INFLUENCE ON JOB SATISFACTION AND ITS IMPLICATIONS ON COMMISSIONERS' PERFORMANCE OF GENERAL ELECTION COMMISSION (KPU) IN WEST JAVA PROVINCE - Zulkarnaen, Wandy; Suteja, Jaja; Arifin, Yusuf (International Journal of Artificial Intelligence Research, 2025)
The aim is to examine the effect of the Integrity on Job Satisfaction and their impact on Commissioner's Performance. Preliminary research shows the poor performance of Commissioner's Performance of the General Election Commission (KPU) of West Java Province, Indonesia. The survey was conducted on 101 respondents consist of commissioner of the General Elections Commission at the district/city level in West Java Province, Indonesia. Data were collected using a questionnaire and data analysis to test the t-test used. The analysis uses partial regression and hypothesis testing using a t-test. All analyzes use statistical tools using Statistical Package for Social Science (SPSS). The results show that the direction of effects of the Integrity (X) on Employee Competency (Y) is positive. Obtained p-value of 0,000 so that the p-value <? = 0.05. That the total effect of Job Satisfaction (Y) on Commissioner's Performance (Z) is .691 or 69.1%. While the remaining 36.7% is the influence of other factors beyond Job Satisfaction. The results showed that the Integrity plays an important role in realizing Job Satisfaction and providing optimal Commissioner's Performance.